Issues Applying Penalties Not Related with Incarceration in Some Foreign Countries (Texas Journal of Multidisciplinary Studies, 2022)
The article analyzes the experience of foreign countries in the use of non-custodial sentences in connection with the liberalization of criminal law. Proposals and recommendations have been put forward to improve the effectiveness of non-custodial sentences.